Fulfillment of Civil Rights and Children's Freedom in Ternate in the Development of a Child-Friendly City - Arisa Murni Rada; Ahmad Mufti (Faculty of Law, Universitas Lampung, 2022)
The existence of children is not only limited to biological and sociological recognition, but it is also critical for the State to formally recognize the existence of a child where they live and stay. It is challenging for children to have a right because they cannot consistently enforce or waive their rights. In contrast, the realization of children's rights is critical in implementing the concept of Child-Friendly Cities. Child-Friendly City is a concept that applies to all communities' governance, including children, large and small, urban and rural. This study was conducted to determine the implementation of the fulfillment of civil rights and children's freedom in Ternate as an indicator of realizing a child-friendly city. Empirical Law research with a conceptual approach and a legal instrument approach was used. The collected data were analyzed descriptively and qualitatively, with conclusions reached using deductive to inductive methods. The findings indicate that the fulfillment of civil rights and children's freedom in several variables has not been fully realized, seen from several examples such as; the low number of children who have access to Child Identity Cards, the formation of children's forums that are not evenly distributed across sub-districts, and the lack of child-friendly information facilities